Profitability and Company Size Have a Strong Influence on Tax Avoidance - Eltie Christi Sandag; Clara Neltje Meini Rotinsulu; Vira Tandiawan; Muhammad Rinaldi (IAIN Palopo, 2022)
This study aims to determine the most dominant influence factor on tax evasion in manufacturing companies. The variables as indicators of this research are Return on Assets and company size. The research was conducted on 28 manufacturing companies from 2019 -2021 which are registered on the IDX, so a total of 84 companies The research method used statistical data processing, namely the determinant test and multiple linear regression. The results showed that the dominant influence on tax evasion was company size.